TRANSFORMASI KEPEMIMPINAN KEPALA DESA DALAM MENGAKSELERASI PEMBANGUNAN DESA - Doli, La; Gazalin, Junaid; Lawelai, Herman (PRAJA: Jurnal Ilmiah Pemerintahan, 2024)
The leadership of the village head has a strong influence in driving village development so that achieves succsess. The leadership of the village head is currently required to be able to realize the village’s vision of becoming a developing and democratic village. Transformasional leadership can anticipate better future conditions so that transformasional leadership is the right leadership model because it is adaptive to a changing environment. So transformasional leadership is needed so that the village’s vision and mission can be achieved. The village head also succeded in increasing the village development index (IDM) score in 2023 to 0.6489. In 2020 the IDM of Lapandewa Kaindea village was at a score of 0.6079. The aim of this research is to find out how the village head’s transformasional leadership improves village development in Lapandewa Kaindea village, Lapandewa District, South Buton Regency. The method used descriptive qualitative with observartion, interviews and document study. The theory used is transformasional leadership theory according to the Bass and Avolio. The data collected is then summarized descriptively and schematically and conclusions are drawn. The village head’s transfomasional leadership is able to improve existing development in Lapandewa Kaindea village, Lapandewa District, South Buton Regency.